Conservation genetics of south american aquatic mammals: An overview of gene diversity, population structure, phylogeography, non-invasive methods and forensics - Rosa de Oliveira, Larissa (2011)
1 Most aquatic mammals have high dispersal potential, and there are often severe conservation concerns related to their legal or illegal harvesting. Therefore, economic, social and forensic factors often arise in decisions relating to their population management. Molecular markers are essential tools in modern conservation genetics, revealing previously unknown aspects of aquatic mammal behaviour, natural history, population structure and demography. Molecular markers also have been used to define management units, to recognize taxonomic units, to conduct forensic analyses and to control illegal wildlife trade, providing valuable information for decision-making in wildlife conservation and management. 2 We review studies published in peer-reviewed journals between 1993 and 2010, in which genetic approaches have been applied to conservation-related issues involving natural populations of 25 species of aquatic mammals in South America. These studies cover just 34% of the 70 aquatic mammal species recorded in South America. 3 Most of the studies are related to population structure, phylogeography, gene flow and dispersal movements. In addition, recent findings relate to evolutionarily significant units, management units, forensics and conservation policy. 4 Finally, we look to the future and, based on numbers of studies and conservation concerns, suggest which species, geographic areas and genetic studies should be prioritized. Moreover, we discuss constraints on research and suggest collaborative works that would provide critical information towards the effective conservation and management of aquatic mammals in South America.